The “Blame-Blame” Syndrome from a Systemic Perspective and Its Implications for Problem Solving in a Company (2018)
The objectives of the study are: to explore systemic structures of the “blame-blame” syndrome in a company, to describe methodologically a playful tool that helps to recognize and mitigate it, and to discuss its implications for causing analysis and problem solving. The ludic exposition includes case description, work team and location, observation scenarios (with and without blaming) and deployment in three test groups. Results are compared for both scenarios and causes of defective orders; percentage of defects and productivity are analyzed. Play can be used by teachers, consultants and trainers in general to confront learners in a simulated environment with and without the syndrome. It makes it easier to systemically reflect on the subject, to identify its signals and intervene before carrying out the cause analysis. This work provides theoretical and empirical elements about the benefits of eradicating the “blame-blame” syndrome in cause analysis, and proposes to consider it as a contingent factor in future studies.